If you come to work at 7:00 and stay 'till 4:15 with a 30 minute lunch - in decimal notation - how many hours did you work?

Answers

Answer 1
Answer:

8.5 hours i think ...............................................................................                                                                                                        


Related Questions

Find the radius and circumference of a cd with a diameter of 4.75 inches
How much compound interest is earned on $4300 at 2.9% interest for 10 years, compounded quarterly?
Sequence 1,2,3,6,18,108 multiply the previous 2 terms to get the next term
In Salem, 82% of the households have cable television and Internet access and 90% of the houses have cable television. What is the probability that a house has Internet access given that it has cable television?A) 8% B) 67% C) 73% D) 91%
The unit rate of change of Y with respect to X is the amount Y changes for a change of one unit in XThe table below represents a proportional relationship with a constant unit rate of change of Y with respect to X Which describes a greater unit rate of change of Y with respect X, the equation y=0.25x or the table? Choose 1 answer: A. The tableB. The equationC. The unit rates are the same

Cual es la raíz cuadrada de 137

Answers

Answer:

11.70469991

Step-by-step explanation:

Which expression is equivalent to x^4 - 12x^2 + 36?(1) (x^2 - 6)(^x2 - 6) (3) (6 - x^2)(6 + x^2)
(2) (x^2 + 6)(x^2 + 6) (4) (x^2 + 6)(x^2 - 6)

Answers

The expression is equivalent to x^4 - 12x^2 + 36 is (x^2 - 6)(x^2 - 6) correct.

We have given that

x^4 - 12x^2 + 36

We have to determine

Which expression is equivalent to x^4 - 12x^2 + 36.

What is the equivalent expression?

Equivalent expressions are expressions that work the same even though they look different. If two algebraic expressions are equivalent, then the two expressions have the same value when we plug in the same value(s) for the variable(s).

(x^2 plus or minus 6)(x^2 plus or minus 6)

an easy way to do this is to only look at plus or minus 6

x^4 - 12x^2 + 36   (-12 and 36)

6 x 6 = 36

6 + 6 ≠ -12            

(x^2 + 6)(x^2 + 6) is incorrect      

6 x -6 ≠ 36

6 + -6 ≠ -12            

(x^2 - 6)(x^2 + 6) is incorrect

-6 x -6 = 36

-6 + -6 = -12      

Therefore the option (x^2 - 6)(x^2 - 6) is correct

The expression is equivalent to x^4 - 12x^2 + 36 is (x^2 - 6)(x^2 - 6) correct.

To learn more about the expression visit:

brainly.com/question/723406

#SPJ2

so the answer is
(x^2 plus or minus 6)(x^2 plus or minus 6)
an easy way to do this is to only look at plus or minus 6
x^4 - 12x^2 + 36   (-12 and 36)

6 x 6 = 36
6 + 6 
≠ -12              (x^2 + 6)(x^2 + 6) is incorrect        

6 x -6 
≠ 36
6 + -6 ≠ -12             (x^2 - 6)(x^2 + 6) is incorrect

-6 x -6 = 36
-6 + -6 = -12         
(x^2 - 6)(x^2 - 6) is correct

the answer is (1)

Is this statement true or false?
Circumference is the distance around the outside of a circle

Answers

true, it is basically the perimeter of the circle

A farmer in china discovers a mammal hide that contains 25% of its original amount of c-14

Answers

Plato answer is 13863


You have left a LOT out of your question.  However I'll attempt to post an answer.

The half-life of carbon 14 is 5,700 years.

If there is 25% of the original carbon 14 remaining that means the time it has undergone has been 2 half lives.

2 half-lives of carbon14 = 2 * 5,700 = 11,400 years.


1.What is the simplified form of each expression?7x^–8 × 6x^3

a. 42/x^5
b. 1/42x^5
c. 42x^11
d. 13x^–5

(–2x8) · 3y9 · 2x4

a. 3x^12y^9
b. –12x^72y^9
c. –12xy^21
d. –12x^y^9

2. Find the simplified form of the expression. Give your answer in scientific notation.

(8 x 10^7) (7 x 10^4)

a. 1.5 × 10^12
b. 5.6 × 10^12
c. 1.5 x 10^29
d. 5.6 x 10^29


(7 × 10^–4)(9 × 10^–10)

a. 6.3 × 10^–13
b. 63 × 10^–13
c. 6.3 × 10^–15
d. 6.3 × 10^–16

Answers

Answer with explanation:

Ques 1)

A)

         We are given a expression as:

    7x^(-8)* 6x^3

It could also be written as:

  (7* 6)* x^(-8)* x^3\n\n\n=42* x^(-8+3)\n\n\n=42x^(-5)\n\n\n=(42)/(x^5)

  Option: a is the answer.

B)

     (-2x^8)* 3y^9* 2x^4

which is solved as follows:

(-2* 3* 2)* x^8* y^9* x^4\n\n\n=-12x^(8+4)* y^9\n\n\n=-12x^(12)y^9

Ques 2)

A)

The expression is:

         (8* 10^7)(7* 10^4)

It is solved as:

  =(8* 7)* 10^7* 10^4\n\n\n=56* 10^(7+4)\n\n\n=56* 10^(11)\n\n\n=5.6* 10^(12)

                 Option: b is the answer.

B)

           (7* 10^(-4))(9* 10^(-10))

On simplifying:

     =7* 9* 10^(-4)* 10^(-10)\n\n\n=63* 10^(-4-10)\n\n\n=63* 10^(-14)\n\n\n=6.3* 10^(-14+1)\n\n\n=6.3* 10^(-13)

                   Option: a is the answer.

What is the soultion to the system of equation graphed below ?

Answers

Hello,
answer D (-2,3)

Indeed
y=4x+11
y=-2x-1

==>4x+11=-2x-1
==>6x=-12
==>x=-2

And y=4*(-2)+11=3